STANDARISASI KOMPOS BERBAHAN BAKU SAMPAH KOTA - Wahyono., dkk, Sri (Jurnal Rekayasa Lingkungan)
Food grade compost should have a high quality such as no containing hazardous andforeign material above of threshold level because of their risk to human and environmental health. So that, compost production should be based on compost standard. In the beginning of this article, the national compost standard No. 19-7030-2004 is discussed. After that we discuss about the principle of compost production, the type of compost technology and the control of composting process.Keywords: Compost quality, municipal salid waste